IMPACT OF HUMAN RESOURCE MANAGEMENT ON ENGAGEMENT AND COMMITMENT IN BANKING WORKPLACES - Kale, Pravin A.; Kediya, Shailesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Researchers examine how Human Resource Management (HRM) policies transform into business applications that influence workplace engagement along with organizational commitment levels in banking institutions. The banking sector faces fast-paced technological transformations together with regulatory and competitive changes while employee expectation alignment with HRM practices has become essential for organizational success. The examination demonstrates that essential HR functions together with recruitment and training as well as performance evaluation and reward processes impact worker emotional commitment to workplace activities. A research method that combines surveys and interviews with bank employees from public and private sectors allows investigation into primary driving factors affecting and disparities between HR policy formation and operational execution. Organizations that successfully turn HRM practices into operational actions achieve substantial boosts in worker dedication training alongside increased workplace productivity alongside lower worker turnover rates. HR leaders need strategic recommendations according to the paper to eliminate policy-practice gaps and develop increased employee engagement in the banking sector.